2020
DOI: 10.1038/s41467-020-15111-4
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting loss of heterozygosity for allele-selective colorectal cancer chemotherapy

Abstract: Cancer chemotherapy targeting frequent loss of heterozygosity events is an attractive concept, since tumor cells may lack enzymatic activities present in normal constitutional cells. To find exploitable targets, we map prevalent genetic polymorphisms to protein structures and identify 45 nsSNVs (non-synonymous small nucleotide variations) near the catalytic sites of 17 enzymes frequently lost in cancer. For proof of concept, we select the gastrointestinal drug metabolic enzyme NAT2 at 8p22, which is frequently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Taken together, our study 7 has identified allelic loss of NAT2 as an event that can be targeted in colorectal cancers with the use of a small molecule. It further suggests that the therapeutic window of targeted therapies can be affected by the presence of bystander mutations in drug metabolic genes.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…Taken together, our study 7 has identified allelic loss of NAT2 as an event that can be targeted in colorectal cancers with the use of a small molecule. It further suggests that the therapeutic window of targeted therapies can be affected by the presence of bystander mutations in drug metabolic genes.…”
mentioning
confidence: 55%
“…In our study, we investigated whether tumor allelic losses arising from LOH events can be exploited for cancer therapy with the use of small molecules. 7 To identify putative targets for a LOH-based therapy, we mapped common variants in the 1000 Genomes project corresponding to 1,092 individuals from 14 different human populations. We focused on single nucleotide variants (SNVs) that: 1) had an allele frequency of at least 0.5%, 2)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several recent strategies seek to target somatic loss of bystander genes located near tumor suppressor genes for cancer therapy 4 10 . We recently reported that LOH at the NAT2 locus on 8p22 can be exploited for therapy using APA, a cytotoxic low molecular weight compound 11 . The NAT2 gene encodes N-acetyltransferase 2, a cytosolic enzyme involved in phase II metabolism of xenobiotics, which is highly polymorphic and has > 100 known single nucleotide variants (SNVs) in the protein coding sequence.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of NAT2 is largely confined to epithelial cells of the gastrointestinal tract and liver, but NAT2 protein has also been detected in lung, bladder and other tissues exposed to exogenous compounds 13 , 14 . Due to chromosome arm LOH at 8p22 during the early development of CRC, a patient heterozygous for a rapid and a slow NAT2 allele may lose the rapid variant in the tumor cells, effectively rendering them deficient in NAT2 activity and sensitive to a cytotoxic substrate of NAT2 11 . As the normal epithelial cells of gut and liver express also the wild-type NAT2 allele, they can evade APA toxicity 11 .…”
Section: Introductionmentioning
confidence: 99%